Introduction to computer-aided solution for shortest-route problems - Sy, Sun Eng (1971)
The main object of this thesis is to introduce locally the use of computer-aided solution in solving shortest path problem. This type of problem is a special case of the more general linear-programming problems and is found relevant in several fields of studies such as in communication engineering. At present, there are several methods available for determining the shortest route through a network. These were briefly discussed. A computer-aided solution of the shortest path problems programmed by the author was then presented and analyzed. Sample calculations using the program were included to show the versatility of computer-aided solution on shortest path problems. Finally, methods of k-best route solution were discussed and the feasibility of computer-aided solutin was investigated.